A high-transmittance double-layer coating solution for photovoltaics and preparation method thereof

By preparing a high-transmittance double-layer coating solution for photovoltaics, the synergy between the modification coupling agent and the europium-doped silica sol was solved, and the photoelectric conversion efficiency of the existing photovoltaic glass was significantly improved.

CN119409427BActive Publication Date: 2025-04-15SHANGHAI DAQIAOKANG NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510035256.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The light transmittance of existing photovoltaic glass is insufficient, resulting in low photoelectric conversion efficiency of solar cells, and the light transmittance of existing double-layer coating solution is still poor, affecting the power generation power of photovoltaic modules.

Method used

A high-transmittance double-layer coating solution for photovoltaic is adopted. By mixing isopropanol, silicon source, water and catalyst, stirring and heating to 50-70°C, and then cooling to room temperature for 3-6 hours, obtaining a silica sol; then mixing the solvent with the silica sol to obtain a first layer of coating solution; then mixing the solvent, silica sol, additive and europium doped silica sol to obtain a second layer of coating solution.

Benefits of technology

Through the synergistic effect of the modification coupling agent and europium-doped silicon sol, the light transmittance of the double-layer coating solution is significantly improved, the utilization rate of solar cell silicon wafers on light quality is improved, and the photoelectric conversion efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a high-transmittance double-layer coating liquid for photovoltaics and a preparation method thereof, and belongs to the technical field of coating liquids. Isopropyl alcohol, a silicon source, water, and a catalyst are mixed, and reacted at 50-70°C for 3-6 hours to obtain a silica sol; the silica sol is mixed with a solvent to obtain a first layer of coating liquid; the first layer of coating liquid is then mixed with a solvent, an auxiliary agent, and a europium-doped silica sol to obtain a second layer of coating liquid. The modified coupling agent stably present in the second coating liquid not only enhances the adhesion between the first film layer and the second film layer, but also the modified coupling agent contains a fluorocarbon long chain, and the fluorocarbon long chain with a higher refractive index can react with the photoluminescent effect Eu 3+ The europium-doped silica sol works synergistically to effectively improve the light transmittance of the double-layer coating solution, thereby effectively improving the utilization of light quality by solar cell silicon wafers and improving photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating liquids, and in particular, relates to a high-transmittance double-layer coating liquid for photovoltaics and a preparation method thereof. Background Art

[0002] Solar cells, also known as photovoltaic cells, are semiconductor devices that convert sunlight directly into electrical energy. They are renewable resources and are green and environmentally friendly. Therefore, they have broad development prospects. The packaging structure of solar cell modules consists of photovoltaic glass, adhesive film, cell sheets and back film. Sunlight needs to pass through photovoltaic glass to perform photoelectric conversion. However, with the current glass preparation process, the light transmittance of photovoltaic glass can only reach about 90%, and 10% of sunlight is still lost, thereby reducing the photoelectric conversion efficiency of solar cells. At present, by coating a layer of coating on the surface of photovoltaic glass, the light transmittance can be increased, thereby increasing the output power of solar cells.

[0003] However, a single-layer coating can only have a good anti-reflection effect on light within a specific wavelength and a narrower band nearby, and the residual reflection is relatively high. Using a refractive index gradient method to perform double-layer or multi-layer coating on the surface of photovoltaic glass can achieve higher anti-reflection in a wide band, a smoother transmittance curve, and better optical performance than a single-layer coating. Chinese patent CN105789340A provides a method for preparing a high-strength double-layer anti-reflection film. The invention first prepares a high-refractive index titanium dioxide sol and a low-refractive index silicon dioxide sol respectively, and then coats a layer of high-refractive index titanium dioxide sol on the surface of the photovoltaic glass. After forming a titanium oxide film, a layer of silicon dioxide film is coated on its surface. Although the double-layer SiO2-TiO2 anti-reflection film obtained by this method has a simple process, the transmittance is still poor, which in turn affects the power generation of photovoltaic modules. Therefore, it is urgent to design and prepare a double-layer coating solution with high transmittance. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-transmittance double-layer coating solution for photovoltaics and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a high-transmittance double-layer coating solution for photovoltaics comprises the following steps:

[0007] (1) Mix isopropanol, silicon source, water and catalyst, stir and heat to 50-70°C, react for 3-6 hours and then cool to room temperature to obtain silica sol;

[0008] (2) mixing the solvent and the silica sol obtained in step (1) to obtain a first coating solution;

[0009] (3) The solvent, the silica sol of step (1), the additive, and the europium-doped silica sol are mixed to obtain a second layer coating solution.

[0010] Furthermore, the silica sol in step (1) comprises the following raw materials in parts by weight: 45-75 parts of isopropanol, 20-40 parts of silicon source, 5-15 parts of water, and 0.001-0.1 parts of catalyst.

[0011] Furthermore, in step (1), the silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, ethyltrimethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.

[0012] Furthermore, in step (1), the catalyst is one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, oxalic acid, and citric acid.

[0013] Furthermore, the first layer coating solution of step (2) comprises the following raw materials in parts by weight: 50-80 parts by weight of solvent and 20-40 parts by weight of silica sol.

[0014] Furthermore, the solvent is one or more of methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, n-butanol, isobutanol, n-pentanol, isopentanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol methyl ether acetate, and ethylene glycol methyl ether acetate.

[0015] Furthermore, the second coating solution of step (3) comprises the following raw materials in parts by weight: 55-75 parts of solvent, 20-30 parts of silica sol, 5-10 parts of auxiliary agent, and 1-2 parts of europium-doped silica sol.

[0016] Furthermore, the auxiliary agent is prepared by the following steps: 75-90 parts of water, 5-15 parts of monomers, 3-6 parts of modified coupling agents, 0.5-2 parts of emulsifiers, and 0.1-1 parts of cross-linking agents are fully stirred by weight, heated to 70-90° C. and reacted for 2-4 hours, 2-4 parts of stabilizer are added, and the mixture is kept warm for reaction for 0.5-2 hours and then cooled to room temperature to obtain the auxiliary agent.

[0017] Furthermore, the monomer is one or more of acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, butyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.

[0018] Furthermore, the modified coupling agent is prepared by the following steps:

[0019] S1. Blow nitrogen into a dry three-necked flask to expel air and moisture from the flask, then add hydroxyethyl methacrylate, 10% sodium hydroxide solution and chloroform, stir evenly and heat to 75°C, then slowly add 3-perfluorooctyl-1,2-propylene oxide, keep warm for 3 hours after the addition is complete, cool to room temperature after the reaction is complete, distill under reduced pressure, wash with deionized water 3 times, and vacuum dry at 110°C for 12 hours to obtain intermediate 1; the dosage ratio of hydroxyethyl methacrylate to 3-perfluorooctyl-1,2-propylene oxide is 14.1mL:27.8mL;

[0020] The molar ratio of hydroxyethyl methacrylate and 3-perfluorooctyl-1,2-epoxypropane is controlled to be 1.1-1.2:1, and the -OH of hydroxyethyl methacrylate and the epoxy group of 3-perfluorooctyl-1,2-epoxypropane react under heating and base catalysis. The reaction process is as follows:

[0021] ;

[0022] S2. Blow nitrogen through a dry three-necked flask to expel air and moisture from the flask, then add intermediate 1, stannous octoate and dimethyl sulfoxide, stir evenly and heat to 80°C, then slowly add 3-isocyanatepropyltrimethoxysilane under stirring, keep warm for 2 hours after the addition is complete, distill under reduced pressure after the reaction is complete, wash with anhydrous ethanol 3 times, and dry under vacuum at 80°C for 12 hours. The entire process is carried out under nitrogen protection to obtain a modified coupling agent; the amount ratio of intermediate 1, 3-isocyanatepropyltrimethoxysilane, stannous octoate and dimethyl sulfoxide is 58.9 g:17 mL:1.1 g:220 mL.

[0023] The molar ratio of intermediate 1 and 3-isocyanate propyl trimethoxy silane is controlled to be 1.05-1.1:1, and the -OH of intermediate 1 and the isocyanate group of 3-isocyanate propyl trimethoxy silane undergo nucleophilic addition reaction under heating and catalysis of stannous octoate. The reaction process is as follows:

[0024] ;

[0025] The modified coupling agent contains a long chain of fluorocarbon, which has a high refractive index and can reduce light reflection, thereby improving light transmittance. The methacrylate group in the modified coupling agent can chemically react with the carbon-carbon double bonds in the monomer to cross-link under the action of the cross-linking agent. Therefore, the modified coupling agent can stably exist in the second layer of coating solution and effectively improve light transmittance. After hydrolysis, condensation and cross-linking, the siloxy group in the modified coupling agent can produce chemical bonding with Si-O-Si or Si-OH in the film layer after the first layer of coating solution is cured, thereby improving the adhesion of the film layer.

[0026] Furthermore, the emulsifier is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, emulsifier OP-10, and glyceryl monostearate.

[0027] Furthermore, the cross-linking agent is one or more of potassium persulfate, ammonium persulfate, and sodium persulfate.

[0028] Furthermore, the stabilizer is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, and hydroxypropyl cellulose.

[0029] Furthermore, the europium-doped silica sol is prepared by the following steps:

[0030] Add europium nitrate hexahydrate (Eu(NO3)3∙6H2O) and deionized water into a beaker, stir until dissolved, then slowly add tetraethyl orthosilicate, stir for 0.5h, then slowly add anhydrous ethanol, mix well, stir at 40°C for 20min, cool to room temperature, add ammonia water to adjust the pH of the system to 7.2, and obtain europium-doped silica sol; the dosage ratio of europium nitrate hexahydrate, tetraethyl orthosilicate, anhydrous ethanol and deionized water is 1.38g:22mL:88mL:63mL.

[0031] Eu doping in silica sol 3+ (trivalent europium ion), and then added to the second layer of coating solution, can use Eu 3+ The photoluminescence effect modulates the energy of the high-energy visible spectrum and converts it into long-wave visible light and near-infrared light that can be used by solar cell silicon devices, effectively improving the utilization rate of light quality by solar cell silicon wafers, thereby improving the photoelectric conversion efficiency. The europium-doped silica sol and the modified coupling agent work together to improve the transmittance of the double-layer coating solution.

[0032] The present invention also discloses a high-transmittance double-layer coating liquid for photovoltaic use, and the double-layer coating liquid is prepared according to the preparation method of the high-transmittance double-layer coating liquid for photovoltaic use.

[0033] The beneficial effects of the present invention are as follows: the modified coupling agent stably present in the second coating solution not only enhances the adhesion between the first film layer and the second film layer, but also the modified coupling agent contains a fluorocarbon long chain, and the fluorocarbon long chain with a high refractive index can react with the Eu containing photoluminescent effect. 3+ The europium-doped silica sol works synergistically to effectively improve the light transmittance of the double-layer coating solution, thereby effectively improving the utilization of light quality by solar cell silicon wafers and improving photoelectric conversion efficiency. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The specific steps for preparing the modified coupling agent are as follows:

[0037] S1. Blow nitrogen into a 250 mL dry three-necked flask to expel air and moisture from the flask, then add 14.1 mL of hydroxyethyl methacrylate, 7.3 mL of 10% sodium hydroxide solution and 110 mL of chloroform, stir evenly and heat to 75°C, then slowly add 27.8 mL of 3-perfluorooctyl-1,2-propylene oxide, keep warm for 3 h after the addition is complete, cool to room temperature after the reaction is complete, distill under reduced pressure, wash with deionized water 3 times, and dry under vacuum at 110°C for 12 h to obtain intermediate 1;

[0038] S2. Blow nitrogen into a 500 mL dry three-necked flask to expel air and moisture from the flask, then add 58.9 g of intermediate 1, 1.1 g of stannous octoate and 220 mL of dimethyl sulfoxide, stir evenly and heat to 80°C, then slowly add 17 mL of 3-isocyanatepropyltrimethoxysilane under stirring, keep warm for 2 h after the addition is complete, distill under reduced pressure after the reaction is completed, wash with anhydrous ethanol 3 times, and dry under vacuum at 80°C for 12 h. The entire process is carried out under nitrogen protection to obtain a modified coupling agent.

[0039] Example 2

[0040] Preparation of europium-doped silica sol, the specific steps are as follows:

[0041] Add 1.38 g of europium nitrate hexahydrate and 63 mL of deionized water into a beaker, stir until dissolved, then slowly add 22 mL of ethyl orthosilicate, stir for 0.5 h, then slowly add 88 mL of anhydrous ethanol, mix well, stir at 40 °C for 20 min, cool to room temperature, add ammonia water to adjust the pH of the system to 7.2, and obtain europium-doped silica sol.

[0042] Example 3

[0043] Preparation of auxiliary agent, the specific steps are as follows:

[0044] 75 parts of water, 2 parts of acrylic acid, 3 parts of butyl methacrylate, 3 parts of the modified coupling agent prepared in Example 1, 0.5 parts of emulsifier OP-10, and 0.1 parts of potassium persulfate were fully stirred by weight, heated to 70° C. for reaction for 4 hours, 2 parts of polyvinyl pyrrolidone were added, and the mixture was kept warm for reaction for 2 hours and then cooled to room temperature to obtain an auxiliary agent.

[0045] Example 4

[0046] Preparation of auxiliary agent, the specific steps are as follows:

[0047] 82 parts of water, 5 parts of methacrylic acid, 5 parts of methyl acrylate, 3 parts of hydroxypropyl methacrylate, 4 parts of the modified coupling agent prepared in Example 1, 1.5 parts of glyceryl monostearate, and 0.8 parts of ammonium persulfate were fully stirred by weight, heated to 80° C. for reaction for 3 hours, 3 parts of polyvinyl alcohol were added, and the mixture was kept warm for reaction for 1.8 hours and then cooled to room temperature to obtain an auxiliary agent.

[0048] Example 5

[0049] Preparation of auxiliary agent, the specific steps are as follows:

[0050] 90 parts of water, 5 parts of acrylic acid, 5 parts of ethyl acrylate, 5 parts of hydroxypropyl acrylate, 6 parts of the modified coupling agent prepared in Example 1, 1 part of sodium dodecyl sulfate, 1 part of sodium dodecylbenzene sulfonate, 0.5 parts of ammonium persulfate and 0.5 parts of sodium persulfate were fully stirred by weight, heated to 90° C. for reaction for 2 h, 2 parts of hydroxypropyl cellulose and 2 parts of polyvinyl alcohol were added, and the mixture was kept warm for reaction for 0.5 h and then cooled to room temperature to obtain an auxiliary agent.

[0051] Example 6

[0052] The specific steps for preparing a high-transmittance double-layer coating solution for photovoltaics are as follows:

[0053] (1) Mix 45 parts of isopropanol, 20 parts of methyl orthosilicate, 5 parts of water, and 0.001 parts of citric acid, stir and heat to 50°C, react for 6 hours, and then cool to room temperature to obtain silica sol;

[0054] (2) mixing 50 parts of propylene glycol methyl ether and 20 parts of the silica sol prepared in step (1) to obtain a first coating solution;

[0055] (3) 55 parts of propylene glycol methyl ether acetate, 20 parts of the silica sol prepared in step (1), 5 parts of the auxiliary agent prepared in Example 3, and 1 part of the europium-doped silica sol prepared in Example 2 were mixed to obtain a second layer coating solution.

[0056] Example 7

[0057] The specific steps for preparing a high-transmittance double-layer coating solution for photovoltaics are as follows:

[0058] (1) 65 parts of isopropanol, 10 parts of ethyl orthosilicate, 15 parts of 3-aminopropyltriethoxysilane, 5 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 12 parts of water, and 0.06 parts of sulfuric acid were mixed, stirred, heated to 65°C, reacted for 4 hours, and then cooled to room temperature to obtain silica sol;

[0059] (2) Mix 20 parts of ethanol, 20 parts of ethylene glycol, 10 parts of propylene glycol ethyl ether, 20 parts of ethylene glycol methyl ether acetate, and 35 parts of the silica sol prepared in step (1) to obtain a first coating solution;

[0060] (3) 20 parts of ethanol, 20 parts of propylene glycol, 25 parts of ethylene glycol methyl ether acetate, 24 parts of the silica sol prepared in step (1), 8 parts of the auxiliary agent prepared in Example 4, and 1.6 parts of the europium-doped silica sol prepared in Example 2 were mixed to obtain a second layer coating solution.

[0061] Example 8

[0062] The specific steps for preparing a high-transmittance double-layer coating solution for photovoltaics are as follows:

[0063] (1) 75 parts of isopropanol, 15 parts of methyl orthosilicate, 5 parts of methyltrimethoxysilane, 10 parts of vinyltrimethoxysilane, 10 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 15 parts of water, 0.1 parts of hydrochloric acid and oxalic acid were mixed, stirred and heated to 70°C, reacted for 3 hours and then cooled to room temperature to obtain silica sol;

[0064] (2) mixing 20 parts of isopropanol, 20 parts of isobutyl alcohol, 20 parts of propylene glycol methyl ether, 20 parts of propylene glycol methyl ether acetate, and 40 parts of the silica sol prepared in step (1) to obtain a first coating solution;

[0065] (3) 20 parts of isopropanol, 20 parts of n-butanol, 20 parts of propylene glycol ethyl ether, 15 parts of ethylene glycol methyl ether acetate, 30 parts of the silica sol prepared in step (1), 10 parts of the auxiliary agent prepared in Example 5, and 2 parts of the europium-doped silica sol prepared in Example 2 were mixed to obtain a second layer coating solution.

[0066] Comparative Example 1

[0067] Preparation of auxiliary agent, the specific steps are as follows:

[0068] The remaining steps remain unchanged, except that the modified coupling agent in Example 3 is replaced by 3-aminopropyltrimethoxysilane to prepare an auxiliary agent.

[0069] Comparative Example 2

[0070] The preparation of double-layer coating solution, the specific steps are as follows:

[0071] The remaining steps remain unchanged, except that the auxiliary agent in step (3) of Example 6 is replaced by the auxiliary agent prepared in Comparative Example 1, thereby preparing a second layer coating solution.

[0072] Comparative Example 3

[0073] The preparation of double-layer coating solution, the specific steps are as follows:

[0074] The remaining steps remain unchanged, and only the europium-doped silica sol in step (3) of Example 6 is removed, thereby preparing the second layer of coating solution.

[0075] Comparative Example 4

[0076] The preparation of double-layer coating solution, the specific steps are as follows:

[0077] The remaining steps remain unchanged, except that the europium-doped silica sol in step (3) of Example 6 is removed and the auxiliary agent is replaced by the auxiliary agent prepared in Comparative Example 1, thereby preparing a second layer of coating solution.

[0078] Performance Testing

[0079] The photovoltaic glass was cleaned, and the first coating liquid prepared in Examples 6-8 and Comparative Examples 2-5 was first coated on the surface, and after solidification into a film, the second coating liquid prepared in Examples 6-8 and Comparative Examples 2-5 was then coated on the film surface, and solidified and tempered to obtain a photovoltaic glass coated with a double-layer coating liquid, and the following performance tests were performed:

[0080] (1) Transmittance

[0081] The photovoltaic glass coated with double-layer coating liquid is placed in a spectrophotometer, and the experimental wavelength range is 380-1100nm. The transmittance of the photovoltaic glass before and after coating is tested, and the transmittance increase value, i.e. the transmittance enhancement value, is calculated by the formula (transmittance increase value = transmittance after coating - transmittance before coating / transmittance before coating × 100);

[0082] (2) Adhesion

[0083] The adhesion of photovoltaic glass coated with double-layer coating liquid is tested using a hundred-grid knife tester. If the cutting edge is completely flush and no grid falls off, it is considered qualified, otherwise it is considered unqualified.

[0084] (3) Dirt resistance

[0085] The pollution source used in the test is prepared ash made of talcum powder as the main component. The suspension is evenly stirred at a ratio of 1:0.9 (mass ratio) and evenly applied to the surface of the photovoltaic glass coated with the double-layer coating liquid. The amount of application is 6g. After being placed in an environment with a temperature of 25°C and a humidity of 50% for 2 hours, the sample is rinsed and placed at a temperature of 25°C and a humidity of 50% until the next day. This is one cycle, about 24 hours. After five cycles of testing according to the above method, if the average value of the effective transmittance of sunlight of the photovoltaic glass coated with the double-layer coating liquid after the test is attenuated by ≤1%, it is recorded as qualified, otherwise it is recorded as unqualified;

[0086] The test results of all items are shown in Table 1 below:

[0087] Table 1

[0088]

[0089] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0090] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-transmittance double-layer coating solution for photovoltaics, characterized in that: The following steps are involved: (1) Mix isopropanol, silicon source, water and catalyst, and react at 50-70°C for 3-6 hours to obtain silica sol; (2) mixing the solvent and the silica sol obtained in step (1) to obtain a first coating solution; (3) mixing the solvent, the silica sol obtained in step (1), the additive, and the europium-doped silica sol to obtain a second coating solution; Wherein, the second layer coating solution comprises the following raw materials in parts by weight: 55-75 parts of solvent, 20-30 parts of silica sol, 5-10 parts of auxiliary agent, and 1-2 parts of europium-doped silica sol; The auxiliary agent is prepared by the following steps: 75-90 parts of water, 5-15 parts of monomers, 3-6 parts of modified coupling agents, 0.5-2 parts of emulsifiers, and 0.1-1 parts of cross-linking agents are stirred and heated to 70-90° C., reacted for 2-4 hours, 2-4 parts of stabilizers are added, the reaction is kept warm for 0.5-2 hours, and cooled to obtain the auxiliary agent; The modified coupling agent is prepared by the following steps: S1, after nitrogen blowing into the flask, add hydroxyethyl methacrylate, sodium hydroxide solution and chloroform, heat to 75°C, add 3-perfluorooctyl-1,2-propylene oxide, react for 3 hours, distill under reduced pressure, wash and dry to obtain intermediate 1; S2. After nitrogen is blown into the flask, intermediate 1, stannous octoate and dimethyl sulfoxide are added, the temperature is raised to 80° C., 3-isocyanatepropyltrimethoxysilane is added, and after reacting for 2 hours, the mixture is distilled under reduced pressure, washed and dried to obtain a modified coupling agent.

2. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: The europium-doped silica sol is prepared by the following steps: Add europium nitrate hexahydrate and deionized water into a beaker, stir, then add ethyl orthosilicate, stir, add anhydrous ethanol, stir at 40°C, cool, and adjust the pH to 7.2 with ammonia water to obtain europium-doped silica sol.

3. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 2, characterized in that: The usage ratio of europium nitrate hexahydrate, tetraethyl orthosilicate, anhydrous ethanol and deionized water is 1.38 g:22 mL:88 mL:63 mL; the usage ratio of hydroxyethyl methacrylate and 3-perfluorooctyl-1,2-propylene oxide in step S1 is 14.1 mL:27.8 mL; the usage ratio of intermediate 1, 3-isocyanatepropyltrimethoxysilane, stannous octoate and dimethyl sulfoxide in step S2 is 58.9 g:17 mL:1.1 g:220 mL.

4. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: The silica sol in step (1) comprises the following raw materials in parts by weight: 45-75 parts of isopropanol, 20-40 parts of silicon source, 5-15 parts of water, and 0.001-0.1 parts of catalyst.

5. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: In the step (1), the silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, ethyltrimethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane; and the catalyst is one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, oxalic acid, and citric acid.

6. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: The first layer coating solution of step (2) comprises the following raw materials in parts by weight: 50-80 parts by weight of solvent and 20-40 parts by weight of silica sol.

7. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: The solvent is one or more of methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, n-butanol, isobutanol, n-pentanol, isopentanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol methyl ether acetate, and ethylene glycol methyl ether acetate.

8. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: The monomer is one or more of acrylic acid, methyl acrylate, ethyl acrylate, butyl methacrylate, and hydroxypropyl acrylate; the emulsifier is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, emulsifier OP-10, and glyceryl monostearate.

9. The method for preparing a high-transmittance double-layer coating solution for photovoltaic use according to claim 1, characterized in that: The cross-linking agent is one or more of potassium persulfate, ammonium persulfate and sodium persulfate; the stabilizer is one or more of polyvinyl pyrrolidone, polyvinyl alcohol and hydroxypropyl cellulose.

10. A high-transmittance double-layer coating solution for photovoltaics, characterized in that: The method for preparing a high-transmittance double-layer coating liquid for photovoltaics according to any one of claims 1-9 is prepared.

Citation Information

Patent Citations

  • Method for preparing high strength double-layer anti-reflection film

    CN105789340A

  • Adhesive laminate

    CN102177213A

  • Film coating liquid for photovoltaic glass double-layer anti-reflection film, and preparation method thereof

    CN110204220A